PHILOSOPHICAL FOUNDATIONS OF WORLD WAR I: THEORY OF COGNITION AND MILITARY STRATEGY - Лобода, Ю. О. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
In the paper “Philosophic groundings of the First World War: theories of cognition and military strategy” was raised a question concerning correlating links between main branches of the European philosophy and peculiarities of military strategies of main participants of the First World War – Great Britain, France, Germany. In the result of the analysis was found out that there are correlative links between peculiarities of philosophic trends of Europe and specificity of their military strategies.